Analyzing Students' Commognitive Processes in Solving Pythagorean Theorem Problems: A Gender-Based - Ain, Nur'; Lefrida, Rita; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra (FKIP Universitas Lampung, 2024)
This study describes students' cognitive in solving Pythagorean theorem problems in terms of gender. The research design used is explorative with a qualitative descriptive approach. The research subjects selected were 2 students, namely 1 male student and 1 female student. Data collection was carried out using written assignments and interviews. Checking the quality of the research results using data credibility is done by extending involvement, increasing persistence, discussions with peers, and membercheck and dependability. Data analysis techniques used in this research are data condensation, data display, and conclusion drawing and verification. The results showed that male and female students had raised all commognitive indicators. Male and female students can generally bring up keywords in the form of the words